2023
DOI: 10.21037/atm-22-4049
|View full text |Cite
|
Sign up to set email alerts
|

Giant pulmonary sclerosing pneumocytoma with potentially malignant biological behavior: a case report and literature review

Wen-Di Zhang,
Zhuang-E Shi,
Meng-Yu Zhang
et al.

Abstract: Background Pulmonary sclerosing pneumocytoma (PSP) is a rare benign lung tumor which generally presents as a solitary pulmonary nodule in middle-aged females. However, the PSP in some patients exhibits potentially malignant biological behavior, with recurrence and lymphatic or distant metastasis being observed. Case Description We encountered a case of a 46-year-old female with an inordinately massive tumor 9.5 cm in diameter and a relatively high Ki-67 proliferation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Cases with multiple nodules, however, even bilateral, have also been reported [ 10 , 11 , 12 , 13 ]. Most of the reported cases show a benign clinical course, but aggressive examples, including cases with distant metastases, also occur [ 4 , 5 , 6 , 14 , 15 , 16 , 17 ]. Wang et al [ 5 ] have detected significant differences in gender, age, and tumor size in PSP with and without metastases.…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases with multiple nodules, however, even bilateral, have also been reported [ 10 , 11 , 12 , 13 ]. Most of the reported cases show a benign clinical course, but aggressive examples, including cases with distant metastases, also occur [ 4 , 5 , 6 , 14 , 15 , 16 , 17 ]. Wang et al [ 5 ] have detected significant differences in gender, age, and tumor size in PSP with and without metastases.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…For example, Teng et al [ 51 ] have reported the malignant transformation of both surface and stromal cells in a PSP with multiple lymph node metastases. Zhang et al [ 14 ] report a PSP measuring 8.9 cm in diameter containing fibrosclerotic areas and hypothesize that the development of tumor metastases might be associated with stromal overgrowth. Actually, a retrospective study has shown that up to 20% of PSPs with dense stromal overgrowth presented lymph node metastases [ 4 ].…”
Section: Prognostic Features Of Concernmentioning
confidence: 99%
See 1 more Smart Citation